2018
DOI: 10.1016/j.ijrmms.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic elastic, strength, and fracture properties of Marcellus shale

Abstract: Shale, a fine-grained sedimentary rock, is the key source rock for many of the world's most important oil and natural gas deposits. A deep understanding of the mechanical properties of shale is of vital importance in various geotechnical applications, including oil and gas exploitation. In this work, deformability, strength, and fracturing properties of Marcellus shale were investigated through an experimental study. Firstly, uniaxial compression, direct tension, and Brazilian tests were performed on the Marce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 91 publications
(89 reference statements)
7
54
0
1
Order By: Relevance
“…Wang et al [18] concluded that the maximum shear strength of shale is 60°based on the experimental data. rough the Brazilian split test and threepoint bending test, Jin et al [19] discussed the anisotropy of shale fracture behavior. Tang and Wu [20] gave the anisotropic crack evolution characteristics of shale and mudstone in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [18] concluded that the maximum shear strength of shale is 60°based on the experimental data. rough the Brazilian split test and threepoint bending test, Jin et al [19] discussed the anisotropy of shale fracture behavior. Tang and Wu [20] gave the anisotropic crack evolution characteristics of shale and mudstone in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Shales show two types of anisotropy: intrinsic (lithological anisotropy, developed from the preferred orientation of platy clay minerals and the development of thin lamination) and stress-induced anisotropy (anisotropy developed with an increase in stress). There are many articles in the literature discussing strength anisotropy (e.g., Jin et al [73], Fjaer and Nes [74]), where the variation of the strength of the rocks with the angle creates problems, especially in inclined wells (e.g., borehole stability). Few researchers have discussed the effects of stiffness, strength, acoustic velocity, and even fracture anisotropy on CO 2 storage or seal integrity.…”
Section: The Petrophysical and Mechanical Characteristics Of Shalementioning
confidence: 99%
“…Different kinds of rocks are plotted in the chart with each kind of rock in a group. The data of 146 specimens used in the chart are all from the literature [19][20][21][22][23][24][25], in which the Young's modulus and the tensile strength are derived from laboratory experiments. Rocks towards the top right have a high value of strength and elasticity and therefore can sustain a higher value of stress.…”
Section: Coal-gas Outburst and Coal Seam Roof Instabilitymentioning
confidence: 99%